2020
DOI: 10.1016/j.geothermics.2019.101722
|View full text |Cite|
|
Sign up to set email alerts
|

Deep basin temperature and heat-flow field in Denmark – New insights from borehole analysis and 3D geothermal modelling

Abstract: We present a 3D numerical crustal temperature model with inverse optimisation methodology and analyse the present-day conductive thermal field of the Danish onshore subsurface. The model is based on a comprehensive analysis and interpretation of borehole and well-log data for thermal and petrophysical rock properties and their regional variability and spatial distribution across the country. New values of terrestrial surface heat flow derived from 21 deep well locations are 65-76 mW•m-2 (mean: 72±3) for the Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 66 publications
(88 reference statements)
0
19
0
Order By: Relevance
“…Indeed, a fine regional understanding of geological setting combined to a detail thermal unit characterization is needed to process with the proposed methodology. Similar work has been achieved in the French Massif Central by Calcagno et al (2014) and in Denmark by Fuchs et al (2020), but with notable differences in the methodology. These authors meshed their 3D geological model to conduct a numerical simulation of steady-state heat conduction using the finite element method to determine temperature in the 3D space.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Indeed, a fine regional understanding of geological setting combined to a detail thermal unit characterization is needed to process with the proposed methodology. Similar work has been achieved in the French Massif Central by Calcagno et al (2014) and in Denmark by Fuchs et al (2020), but with notable differences in the methodology. These authors meshed their 3D geological model to conduct a numerical simulation of steady-state heat conduction using the finite element method to determine temperature in the 3D space.…”
Section: Discussionmentioning
confidence: 68%
“…Relatively small-scale 3D geothermal models, on the order of ≤100 km in diameters, are described in the literature with non-exhaustive examples from around the world including Denmark, Germany, Iceland, Italy, New Zealand, The Netherlands, the United States of America and Taiwan (e.g. Guglielmetti et al, 2013;;Chang et al, 2014;Gasperikova et al, 2015;Ratouis et al, 2016;Siler et al, 2016;Przybycin et al, 2017;Békési et al, 2020;Fuchs, 2020). On the other hand, regional or large-scale 3D models, on the order of >100 km diameters, are just starting to be used for the assessment of geothermal resources.…”
Section: Introductionmentioning
confidence: 99%
“…The main inaccuracies of our model in northern England relate to geological inputs, such as bedrock and superficial cover. Fuchs and Balling (2016) and Fuchs et al (2020) discuss the importance of geological constraints and their regional variability for subsurface temperature models such as these. Other inaccuracies may relate to fluid convection.…”
Section: Discussionmentioning
confidence: 99%
“…Research at the University of Aarhus in conjunction with GEUS has shown that the temperature gradient is typically 25-30°C km −1 without pronounced temperature anomalies. The temperature distribution is fairly well understood and the observed variations in temperature gradients are mainly owing to differences in thermal conductivity of the geological strata (Fuchs et al, 2015;Fuchs & Balling, 2016;Poulsen et al, 2017;Fuchs et al, 2020). Simulations of the production lifetime of a geothermal plant show that it can take many decades before a notable temperature drop can be detected if production and injection wells are separated more than 1000 m in reservoirs with transmissibilities in the 10þ Dm range and operated at rates of 100-200 m 3 h −1 (Poulsen et al, 2017).…”
Section: Geological Backgroundmentioning
confidence: 99%